Comparative analyses of eight complete plastid genomes of two hemiparasitic Cassytha vines in the family Lauraceae - Yu, Qun-Fei; Tan, Yun-Hong; Yu, Wen-Bin; Yang, Shi-Ting; Huang, Jie-Peng; Caraballo-Ortiz, Marcos A.; Liu, Chao; Song, Yu (Frontiers in Genetics, 2023)
Cassytha is the sole genus of hemiparasitic vines (ca. 20 spp.) belonging to the Cassytheae tribe of the Lauraceae family. It is extensively distributed in tropical and subtropical regions. In this study, we determined the complete plastid genome sequences of C. filiformis and C. larsenii, respectively, which do not possess the typical quadripartite structure. The length of C. filiformis plastomes ranged from 114,215 to 114,618 bp, whereas that of C. larsenii plastomes ranged from 114,900 to 114,988 bp. Comparative genomic analysis revealed 1,013 mutation sites, four large intragenomic deletions, and five highly variable regions in the eight plastome sequences. Phylogenetic analyses based on 61 complete plastomes of Laurales species and trnK barcodes from 83 individuals of Cassytha spp. confirmed a non-basal group comprising individuals of C. filiformis, C. larsenii, and C. pubescens in the family Lauraceae and proposed a sister relationship between C. filiformis and C. larsenii. Further morphological comparisons indicated that the presence or absence of hairs on the haustoria and the shape or size of fruits were useful traits for differentiating C. filiformis and C. larsenii.